2016
DOI: 10.21037/jtd.2016.09.14
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection for partial breast irradiation by intraoperative radiation therapy: can magnetic resonance imaging be useful?—perspective from radiation oncology point of view

Abstract: The guidelines of the European and American Societies of Radiation Oncology (GEC-ESTRO and ASTRO) defined the selection criteria to offer partial breast irradiation (PBI) after lumpectomy in patients with low risk breast cancer regardless pre-operative staging. A recent publication by Tallet et al.explored the impact of preoperative magnetic resonance imaging (MRI) on patient eligibility for PBI. From their study, an ipsilateral BC was detected in 4% of patients, excluding these patients from intraoperative ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…MRI precisely defines tumor size, unifocality, and presence of lymph nodes with a sensitivity of around 100%, especially in dense breasts. [35][36][37] Tallet et al [38] demonstrated that a preoperative MRI can aid in detecting 31% more breast abnormalities which were not visible on mammography or ultrasound. Although not mandatory, a preoperative MRI should be encouraged for patients who chose to receive IORT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI precisely defines tumor size, unifocality, and presence of lymph nodes with a sensitivity of around 100%, especially in dense breasts. [35][36][37] Tallet et al [38] demonstrated that a preoperative MRI can aid in detecting 31% more breast abnormalities which were not visible on mammography or ultrasound. Although not mandatory, a preoperative MRI should be encouraged for patients who chose to receive IORT.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to incorporate high resolution images, such as Magnetic resonance imaging (MRI), to screen, and filter out unsuitable candidates at the beginning. MRI precisely defines tumor size, unifocality, and presence of lymph nodes with a sensitivity of around 100%, especially in dense breasts [35–37] . Tallet et al [38] demonstrated that a preoperative MRI can aid in detecting 31% more breast abnormalities which were not visible on mammography or ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…One approach is that patients can undergo intra‐operative RT (IORT) at the time of breast‐conserving surgery. Preoperative bilateral breast MRI can detect occult lesions in the ipsilateral and contralateral breasts, and provide a valuable tool in the proper selection of patients best suited for IORT 135–137 . Even in highly selected, favorable risk patients, MRI‐detected additional lesions may change surgical and RT recommendations in a substantial percentage of patients 135 .…”
Section: Mpmri In Rt Treatment Response Assessmentmentioning
confidence: 99%
“…Preoperative bilateral breast MRI can detect occult lesions in the ipsilateral and contralateral breasts, and provide a valuable tool in the proper selection of patients best suited for IORT. [135][136][137] Even in highly selected, favorable risk patients, MRI-detected additional lesions may change surgical and RT recommendations in a substantial percentage of patients. 135 Another approach of APBI is pre-operative delivery of external beam irradiation in a single or fractionation delivery.…”
mentioning
confidence: 99%